Applying Reverse Supply Chain in the Poultry Industry - Shamsuddoha, Mohammad (2011)
As concern for the environment grows, the concept of reverse supply chain has gained increasing attention in business and academic circles. Attention to supply chain management has progressively amplified since the 1980s when firms realized mutual profitable relationships within and beyond their own organizations. In time, reverse supply chain issues also came to the fore with the focus on the environment, product return back, waste reduction, recycle and re-use. In this research project, the existing poultry industry in Bangladesh is used as a case study to explore a new model for reverse supply chain management. The objectives of this paper are twofold; first, it offers a review on existing reverse supply chain literature; second, it offers a conceptual reverse supply chain process model in the light of poultry industries in Bangladesh. The model has been developed through taking in-depth interviews with leading poultry entrepreneurs. The paper also focuses on three Rs (Recycle, Reuse, and Reduce) of reverse supply chain along with supply chain management in the root of poultry industry.